Relationships of Illness Perceptions with Depression and Anxiety in People Who Live with HIV/AIDS in a High-prevalence Ethnic Autonomous Region of Sichuan, China - Feng, Chuanteng; Yu, Bin; Fu, Yao; Reinhardt, Jan D.; Yang, Shujuan (AIDS and behavior, 2022)
Poor mental health challenges outcomes and treatment of people living with HIV/AIDS (PLWHA) and may be related to illness perceptions. To investigate if depression and anxiety were associated with illness perceptions, we drew a random sample of 729 PLWHA from 13 administrative units in Liangshan Prefecture, Sichuan, China. Among the PLWHA surveyed, 222 and 175 had probable anxiety or depression. In mixed-effects logistic regression, negative illness perceptions were associated with increased odds of anxiety/depression. In linear mixed-effects quantile regression, the relationship of more negative illness perceptions with more severe and frequent symptoms of anxiety/depression grew stronger in the upper quantiles of the GAD-7 and PHQ-9 distributions, well beyond scale cut-offs for probable clinical relevance. We hypothesize that negative illness perceptions of HIV/AIDS and severity of depression and anxiety symptoms may mutually reinforce each other. Illness perceptions are a promising intervention target for improving the mental health of PLWHA.